2013
DOI: 10.1007/s11274-013-1291-7
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory capacity of the Kluyveromyces marxianus yeast isolated from the mezcal process during oxidative stress

Abstract: During the mezcal fermentation process, yeasts are affected by several stresses that can affect their fermentation capability. These stresses, such as thermal shock, ethanol, osmotic and growth inhibitors are common during fermentation. Cells have improved metabolic systems and they express stress response genes in order to decrease the damage caused during the stress, but to the best of our knowledge, there are no published works exploring the effect of oxidants and prooxidants, such as H2O2 and menadione, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 33 publications
0
14
0
1
Order By: Relevance
“…Our previous fermentation indicated the delay of the process under relatively anoxic conditions and in turn an appropriate aeration volume promoted cell growth and ethanol production. From yet another angle, aeration resulted in the production of toxic compounds, called reactive oxygen species (ROS), including superoxide, peroxide, hydroxyl radical, and so on [ 35 , 36 ]. As a consequence, a thorough protective mechanism exists in K. marxianus Y179 cells to protect it from damage by ROS.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous fermentation indicated the delay of the process under relatively anoxic conditions and in turn an appropriate aeration volume promoted cell growth and ethanol production. From yet another angle, aeration resulted in the production of toxic compounds, called reactive oxygen species (ROS), including superoxide, peroxide, hydroxyl radical, and so on [ 35 , 36 ]. As a consequence, a thorough protective mechanism exists in K. marxianus Y179 cells to protect it from damage by ROS.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that the K. marxianus SLP1 is a thermotolerant yeast. Arellano-Plaza et al 4 reported that MC4 showed the higher viability when the same yeast strains were exposed to oxidative stress. These results suggest that stress resistance differs in the same yeast strain depending on the stressor.…”
Section: Discussionmentioning
confidence: 99%
“…These conditions could apply a natural selection pressure on yeast to evolve into thermotolerant strains. Arellano-Plaza et al 4 reported that the Saccharomyces cerevisiae (MC4) and Kluyveromyces marxianus (OFF1 and SLP1) yeast strains were able to resist oxidative stress for a long period of time compared with W303-1A ( S. cerevisiae reference strain). The MC4, OFF1, and SLP1 yeast strains were isolated from spontaneous mezcal fermentation carried out at handcraft mezcal distilleries in Oaxaca, San Luis Potosí, and Guerrero (all Mexican states).…”
Section: Introductionmentioning
confidence: 99%
“…Under certain conditions, ROS generated from cell metabolism causes more cell damages, and ROS generally includes super oxide, peroxide, and hydroxyl radical et al [ 32 ]. In order to prevent from ROS damages, microorganisms build a perfect defense system, which involves some essential oxidoreductases and compounds, such as peroxiredoxins (Prxs), thioredoxin ( TRX ) and its reductase ( TrxR ), glutathione and its reductase ( GLR ) and peroxidase ( GPX ), catalase ( CTT1 ), and superoxide dismutase ( SOD ) (Fig.…”
Section: Discussionmentioning
confidence: 99%